2004
DOI: 10.1081/ncn-120027816
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Mass Spectrometry for Structure Assignments of Wye Nucleosides from Transfer RNA

Abstract: The tricyclic wye nucleoside family of eight known members constitutes one of the most complex and interesting series of posttranscriptionally modified nucleosides in transfer RNA. The principal reaction paths represented in collision-induced dissociation mass spectra of wye bases and their analogs have been studied in order to determine those structural features that can be readily established by mass spectrometry. The main routes of fragmentation are determined by the presence vs. absence of an amino acid si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The protonated base fragment (BH 2 + ) of the each tRNA was selected as a parent mass and decomposed in collision with helium gas to obtain the spectrum of product ions (Supplementary Figure S3). Most of our data could be interpreted by referring to the CID spectra for chemically synthesized yW derivatives, part of the pioneering work by J McCloskey's group (Zhou et al , 2004a, 2004b). Interpretation of each CID spectrum and determination of chemical structure of each yW intermediate are described in the legend for Supplementary Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…The protonated base fragment (BH 2 + ) of the each tRNA was selected as a parent mass and decomposed in collision with helium gas to obtain the spectrum of product ions (Supplementary Figure S3). Most of our data could be interpreted by referring to the CID spectra for chemically synthesized yW derivatives, part of the pioneering work by J McCloskey's group (Zhou et al , 2004a, 2004b). Interpretation of each CID spectrum and determination of chemical structure of each yW intermediate are described in the legend for Supplementary Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…After thin layer chromatography (Fig. 3), a single fluorescent spot (R F ϭ 0.47) 5 was detected in extracts prepared from the wild-type strain, and mass spectrometric analysis of this fluorescent material gave a mass of 377.1 Da corresponding to that of yW (57). Extracts from the ⌬YPL207w deletion strain lacked the fluorescent material.…”
Section: Identification Of Cog0731 As a Probable Wyebutosine Synthesimentioning
confidence: 99%
“…The authors also observed facile loss of a CH 3 -radical from other protonated wye bases and explained this uncommon loss by charge stabilization and radical delocalization through the nitrogen-rich tricyclic ring [45].…”
Section: Resultsmentioning
confidence: 99%